"Motherhood Is Beautiful": Maternalism in the West German New Women's Movement between Eroticization and Ecological Protest. Issue 4 (December 2020) - Schmacks, Yanara
Abstract: This article traces changing conceptions of maternalism in the West German New Women's Movement from the early 1970s to the late 1980s. I argue that there were two moments in which the concept of motherhood was heatedly discussed and transformed. First, from the mid-1970s onward and within the broader cultural currents of "New Inwardness" ( Neue Innerlichkeit ) and "New Sensuality" ( Neue Sinnlichkeit )—both of which permeated the New Left—motherhood became sensualized, eroticized, and sexualized. Second, these trends were intensified and at the same time drawn into new directions after the 1986 Chernobyl catastrophe. For while the focus on female corporeality was consolidated, a growing ecofeminist strand successfully reimagined motherhood as tightly bound to nature and life itself. Serving also as a means to deal with the Nazi past, this late 1980s conception of motherhood was marked by a more pessimistic, even apocalyptic outlook.